2005
DOI: 10.1534/genetics.104.033597
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Analysis of Introgression Between Two Sympatric Sister Species of Drosophila:Drosophila yakubaandD. santomea

Abstract: Drosophila yakuba is widely distributed in sub-Saharan Africa, while D. santomea is endemic to the volcanic island of São Tomé in the Atlantic Ocean, 280 km west of Gabon. On São Tomé, D. yakuba is found mainly in open lowland forests, and D. santomea is restricted to the wet misty forests at higher elevations. At intermediate elevations, the species form a hybrid zone where hybrids occur at a frequency of 1%. To determine the extent of gene flow between these species we studied polymorphism and divergence pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
201
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(226 citation statements)
references
References 93 publications
21
201
4
Order By: Relevance
“…This signature is often interpreted as evidence for population expansion (e.g., Machado et al 2002;Glinka et al 2003;Das et al 2004;Llopart et al 2005). However, a negative mean Tajima's D is expected under a variety of population genetic models (see Tajima 1989b;Braverman et al 1995;Charlesworth et al 1995;Gillespie 1997;Tachida 2000;Haddrill et al 2005b).…”
Section: Resultsmentioning
confidence: 99%
“…This signature is often interpreted as evidence for population expansion (e.g., Machado et al 2002;Glinka et al 2003;Das et al 2004;Llopart et al 2005). However, a negative mean Tajima's D is expected under a variety of population genetic models (see Tajima 1989b;Braverman et al 1995;Charlesworth et al 1995;Gillespie 1997;Tachida 2000;Haddrill et al 2005b).…”
Section: Resultsmentioning
confidence: 99%
“…No genetic cluster identified using nuclear data had just a single haplotype group, and the most divergent lineage, Cluster I, possessed a particularly heterogeneous mixture of both haplotype groups. The most parsimonious explanation for such patterns is that mitochondrial genomes have been captured by non-ancestral lineages (e.g., Llopart et al 2005). Likewise, the two divergent morphological types (vittigera and typica) also appear to have Divergence between clusters II and III probably represents a more recent repeat of the above: again, two lineages diverge and begin to sort mitochondria and morphology but continue to experience gene flow without lineage fusion moved between lineages, given that two of the three races contained a mix of both vittigera and typica morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed major alterations of meiotic pairing leading to distortions in recombination frequencies (Zhang et al, 1999). For example, Llopart et al (2005) found that the degree of introgression between Drosophila yakuba and D. santomea depends on the region in the genome and the associated recombination rate. Recombination between divergent genomes in hybrids may be selectively disadvantageous, because it often leads to hybrid dysgenesis, with a proportionally large effect of the sex chromosomes (Coyne and Orr, 2004).…”
Section: Discussionmentioning
confidence: 99%